Simultaneous nodular lymphocyte-predominant Hodgkin lymphoma with papillary thyroid carcinoma: a case report. Issue 12 (30th December 2022) - Murayama, Daisuke; Hashizume, Toko; Hirano, Ryosuke; Azuhata, Koji; Shimojo, Hisashi; Ito, Nobuo; Mishima, Osamu
Abstract: We herein report the case of a 48-year-old man diagnosed with nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL, Stage IA) and papillary thyroid carcinoma (PTC, Stage I). Total thyroidectomy, left modified neck dissection and biopsy of the right cervical lymph node were performed. Postoperatively, NLPHL treatment was prioritized, and external radiation (30.6 Gy) was applied to the right neck. PTC was considered a high-risk category for recurrence due to extranodal invasion of lymph node metastasis, and radioactive iodine therapy (ablative dose, 1110 MBq) was administered. Both PTC and NLPHL showed no recurrence 18 months after surgery.